Physichochemical properties of Khaki Campbell, Muscovy and Pekin duck feet gelatin extracted with acetic acid - Fatin Arina Mohd Zain; Norshazila Shahidan; Nurul Huda; Zarinah Zakaria; Abdi Wira Septama (2020)
Gelatin is a high molecular weight polypeptides with water soluble properties that was derived from collagen by thermal treatment hydrolysis (Bailey & Light., 1989; Kuan et al., 2016). The major source of gelatin production in Europe is 60% from pigs and another 40% of gelatin production are from bones and skin of cattle and other animal (Aykin-Dinçer et al., 2017). Nevertheless, the market for non-porcine and non-bovine gelatin has been increased recently by Kosher, Muslims and Vegetarian regarding the halal food issue and occurrence of diseases from bovine such as Bovine Spongiform Encephalopathy (BSE) and food and mouth diseases (FMD) (Karim & Bhat., 2009; Samsudin et al., 2018). Hence, another alternatives to gelatin is from mammalian-derived source such as avian sources for example from duck feet (Kuan et al., 2016).